2020
DOI: 10.1007/s00520-020-05800-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a plain-language guide for discussing breast cancer genetic counseling and testing with patients with limited health literacy

Abstract: Purpose Due to limited health literacy and resulting ineffective communication between healthcare professionals and patients, not all eligible patients are offered breast cancer genetic counseling and testing. We aimed to develop a plain-language guide to increase effective communication about genetic counseling and testing with breast cancer patients with limited health literacy. Methods Together with oncological healthcare professionals, we drafted a list of jargon words frequently used during (breast) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…These findings highlight the need for developing accessible information resources, using plain language, to support communication with patients about HBC and its implications for relatives. Whilst resources have been developed for use in HICs, research is needed to co-develop similar resources locally with HCPs and BC patients with low literacy and for use in a context with limited access to genetic testing (van der Giessen et al 2021;Ahmed et al 2022). To further enable patient access, such information resources should be developed in written, audio, and video formats.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the need for developing accessible information resources, using plain language, to support communication with patients about HBC and its implications for relatives. Whilst resources have been developed for use in HICs, research is needed to co-develop similar resources locally with HCPs and BC patients with low literacy and for use in a context with limited access to genetic testing (van der Giessen et al 2021;Ahmed et al 2022). To further enable patient access, such information resources should be developed in written, audio, and video formats.…”
Section: Discussionmentioning
confidence: 99%
“…For successful language accommodation, plain language needs to be taught systematically in health communication courses in dental education in Japan. There is a growing body of evidence indicating that the incorporation of plain language training into medical education has positive implications for oral and written communication skills, such as breast cancer genetic counseling [ 20 ] and discharge letters [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Warde et al noted that the aim of this approach was not to oversimplify the health information, but rather to convey essential information in a simple, succinct, and accurate manner [ 16 ]. Previous studies reported the development of plain language communication training in medical education [ 18 , 19 , 20 ]. For example, Bittner et al provided a newly established course for patient-centered communication, which incorporated the translation practice of medical reports into plain language under near-peer supervision [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, 46% of 90 surveyed neurologists rated PLS as ‘valuable’ and 60% would use PLS with their patients, noting that PLS streamline dialogue (Pushparajah et al, 2018). Further, from a cohort of 58 surveyed oncologists and genetic counsellors, 57% indicated they would use plain language guides with patients and 65% would share with colleagues; overall perceived acceptability and utility for informing patient communications was high (van der Giessen et al, 2021).…”
Section: The Value and Impact Of Pls And Plsps For Enabling Diversity...mentioning
confidence: 99%